Pengaruh Pembelajaran IPA Menggunakan Model PBL Berbantuan Video Animasi Terhadap Keterampilan Proses dan Hasil Belajar Kognitif Siswa Kelas V - Permata Ayunani, Angela; Widi Winarni, Endang; Muktadir, Abdul (Jurnal Kajian Pendidikan Dasar, 2025)
The purpose of this research is to analyze the influence of science learning using the Problem Based Learning model assisted by animated video media on process skills and cognitive learning outcomes. The type of research used is quasi-experimental research employing The Matching Only Pretest-Posttest Control Group Design. The type of data used is quantitative data, specifically using question instruments and expert validation sheets. Based on the research results, it was found that the application of science learning using the Problem Based Learning model assisted by animated video media has a significant effect on process skills. This is indicated by the average posttest process skills score in the control class being 32.9. Meanwhile, the average posttest score in the experimental class is 85.75. The application of science learning using the Problem Based Learning model assisted by animated video media has a significant effect on cognitive learning outcomes. This is indicated by the average posttest cognitive learning outcomes score in the control class being 33. Meanwhile, the average posttest score in the experimental class is 86. There is no correlation between the aspect of process skills and cognitive learning outcomes.